The effect of nursing care provided to coronary intensive care patients according to their circadian rhythms on sleep quality, pain, anxiety, and delirium: a randomised controlled trial - Meryem Pelin; Havva Sert (BMC Nursing)
Abstract Aim This study carried out to examine the effects of nursing care given to coronary intensive care patients according to their circadian rhythms on sleep quality, pain, anxiety, and delirium. Study Design This study was designed as a randomised controlled, clinical investigation. The study population consisted of patients treated in the coronary care unit of a training and research hospital between September 2022 and February 2023. Total of 44 participants were included. The included participants were followed up for 3 days in the coronary intensive care unit. Data were collected using “Patient Information Form, Sleep Quality Scale in Coronary Intensive Care Patients (SQ-CC), Visual Analogue Scale (VAS), Morningness-Eveningness Questionnaire (MEQ), Hospital Anxiety and Depression Scale (HADS), Intensive Care Delirium Screening Checklist (ICDSC).” In addition, melatonin and cortisol measurements were made, and sleep data were taken with a smartwatch. Patients with intermediate chronotype, delirium, on ventilator support, or using sedative drugs were excluded. The chronotypes of the participants were determined, and the patients in the intervention group were given nursing care by their circadian rhythms. No intervention was made to the control group, and their routine care was continued in accordance with intensive care unit functioning. Frequency distribution, dependent and independent sample t-test, Wilcoxon test, repeated measures analysis of variance, Mann Whitney U, and chi-square analysis were used to evaluate the data. The study has been registered in ClinicalTrials.gov (Identifiers: NCT04934436). During statistical analysis, the groups were coded as Group A and Group B, ensuring blinding for the statistician. Results The intervention group’s sleep quality increased compared to the control group (post-test SQ-CC total scores: intervention group 22.41 ± 6.67 vs. control group 50.45 ± 10.63, p < 0.001). Although no significant difference was found between the groups as a result of the study, there was a significant decrease in the pain score in the intervention group (VAS pre-test: 1.55 ± 2.15, post-test: 0.68 ± 2.21, p = 0.036). The anxiety of the intervention group decreased significantly compared to the control group (post-test HADS-Anxiety scores: intervention group 3.18 ± 3.29 vs. control group 8.50 ± 5.66, p = 0.001). The post-test delirium score was higher in the control group compared to the intervention group (post-test ICDSC scores: intervention group 0.32 ± 0.48 vs. control group 1.18 ± 0.50, p < 0.001). Melatonin increased and cortisol decreased in both groups without statistically significant differences between them (melatonin and cortisol levels: p > 0.05). Considering the sound levels in the environment, the first-night decibel mean was significantly higher in the intervention group than in the control group (first-night decibel mean: intervention group 56.58 ± 2.43 dB vs. control group 54.51 ± 2.41 dB, p < 0.05). Finally, the smartwatch data show no significant difference in sleep times between groups (p < 0.05), but the intervention group had more deep and total sleep, while the control group had less deep sleep. Conclusions Nursing care given in accordance with the circadian rhythm increases sleep quality and reduces the risk of delirium and anxiety in patients followed up with acute coronary syndrome in the coronary intensive care unit.